Analisis Koordinasi Over Current Relay Dan Recloser Pada Sistem Distribusi 20kv Penyulang Palur12 Menggunakan Etap 12.6 - Kurniawan Saputro, Azanto, Umar,ST.MT (2016)
Short circuit interruption that often occur at the distribution system 20KV can cause distruption of the distribution of electrical energy to the consumer. This short circuit interruption can be resolved by doing the coordination of protection at distribution system 20KV to isolate the interference well and protect the equipment at distribution system 20KV. Coordination between over current relay on side of incoming or outgoing at Penyulang Palur 12 and recloser as a primary protection must be exact and appropriated. The purpose of this research is to know the over current relay and recloser settings more appropriated based of the short circuit which happens at distribution system 20KV Penyulang Palur12. Setting time of over current relay on incoming side(0,7) over current relay on outgoing side(0,5) and recloser(0,3) agree with IEE 242-1986 standard whch have minimal time setting is 0,3 second. Research begins with collection electrical data at penyulang Palur 12. And then determine the setting of over current relay and recloser. Then illustrate the curve of coordination over current relay and recloser. The protection's place more further from the powergrid, setting of the current and time should be getting smaller.